Morphic resonance : the nature of formative causation - Sheldrake, Rupert (Rochester, Vt. : Park Street Press, 2009)
"New updated and expanded edition of the groundbreaking book that ignited a firestorm in the scientific world with its radical approach to evolution"--Provided by publisher.
Str. 266-306: Bibliografske bilješke
Str. 292-306: Bibliografija
Kazala
Keywords: život; podrijetlo